Mixed Ligand Complexes: Synthesis and Characterization Studies (Faculty of Education Scientific Journal, 2023)
The synthesis and structural characterization of mixed ligand complexes of Schiff base derived from the condensation of 2-hydroxyacetophenone and 2,4-dinitrophenylhydrazine (HL1) and 2-aminophenol(L2) are reported. The ligands and their mixed ligand complexes were characterized on the bases of their IR, 1HNMR, UV-Vis, elemental analyses, magnetic moment and molar conductance measureents. The mixed ligand complexes under investigation were formed in the 1:1:1 or 1:1:2 [M:L1:L2] ratio as found from the elemental analysis data and found to have the formulae [L1ML2(H2O)2], where M = Mn(II), Fe(III), Co(II) and Ni(II) ions and [L1Cr(L2)2], The molar conductance results revealed that the complexes are non-electrolytes. IR spectra showed that the ligands are coordinated to the metal ions in a bidentate manner with donor sites. Magnetic moments are used to infer the coordinating capacity of the ligands and the geometrical structure of their complexes are found to be  an octahedral.